Anticorpos contra Leptospira spp. e Brucella spp. em equiídeos da região Sul do Brasil abatidos em matadouro-frigorífico - Santos, Renata Bossolani Ferreira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The goal of this study was to investigate the presence of antibodies against Leptospira spp. and Brucella spp. in sera samples of horses slaughtered in an abattooir, under the Brazilian federal food inspection service, located in the south region of Brazil. Serum samples from 767 adult horses, males (n = 407) and females (n = 360) slaughtered from April to May 2013, were analyzed. The animals came from 45 municipalities in the states of Rio Grande do Sul, Santa Catarina and Paraná. The microscopic agglutination test (MAT) was used for the diagnosis of leptospirosis. For brucellosis diagnosis, the rose bengal plate test (RBPT) was used as screening, and fluorescence polarization assay (FPA), reaction complement fixation (CFR) and 2-mercaptoethanol (2-ME) were used as confirmatory tests. Seropositivity was observed in 687 (89.57%; 95% CI: 87.41 % - 91.73 %) horses, that had antibodies to at least one of the 24 serovars of Leptospira spp. at a titer greater than or equal to 100. The predominant serovars were Patoc (56.71%), Bratislava (50.07%), Butembo (39.11%) and Icterohemorrhagiae (33.38%). There was no significant difference (p = 0.2795) between the proportions of reactors to Leptospira spp. in the states. Regarding the proportion of males and females reagents, the difference was highly significant (p = 5.4444 x 10-5); 85.26% (95% CI: 82.82% - 88.70%) of the males and 94.44% (95% CI: 92.07% - 96.81%) of the females tested positive to Leptospira. In the RBPT, 65 (8.47%) animals tested positive, and only two (3.07 %) of them were also positive in CFR and three (4.62%) were positive in FPA. The results obtained in this study show a high exposure of the horses to several serovars of Leptospira. Despite the low frequency of animals positive for Brucella spp., it can be said that the infection in horses is present in the study area, what is demonstrated by the presence of reacting animals. Regarding ...

Objetivou-se investigar a presença de imunoglobulinas anti- Leptospira spp. e anti-Brucella spp. em amostras de soros sanguíneos de equídeos abatidos em matadouro-frigorífico, sob Serviço de Inspeção Federal, localizado na região Sul do Brasil. Utilizaram-se 767 amostras de sangue de equídeos adultos, machos (n = 407) e fêmeas (n = 360), abatidos no período de abril a maio de 2013. Os animais foram provenientes de 45 municípios dos Estados do Rio Grande do Sul, Santa Catarina e Paraná. Para o diagnóstico de leptospirose foi utilizado o teste de soroaglutinação microscópica (SAM), e para brucelose, os testes do antígeno acidificado tamponado (AAT), sendo os resultados positivos confirmados pelos testes de polarização fluorescente (TPF), reação de fixação de complemento (RFC) e 2- mercaptoetanol (2-ME). Foram observados 687 equídeos sororreagentes a pelo menos uma das 24 sorovariedades utilizadas de Leptospira spp. com título igual ou superior a 100, representando 89,57% (IC 95%: 87,41% - 91,73%). As sorovariedades predominantes foram Patoc (56,71%), Bratislava (50,07%), Butembo (39,11%) e Icterohemorrhagiae (33,38%). Não houve diferença significativa (p = 0,2795) entre as proporções de reagentes a Leptospira spp. nos estados. Já em relação à proporção de machos e fêmeas reagentes houve diferença altamente significativa (p = 5,4444 x 10-5), sendo 85,26% (IC 95%: 82,82% - 88,70%) de machos reagentes e 94,44% (IC 95%: 92,07% - 96,81%) de fêmeas reagentes. Foram sororreagentes no AAT 65 (8,47%) animais. Destes, apenas dois (3,07%) foram positivos também na RFC e três (4,62%) animais foram positivos no TPF. Os resultados obtidos no presente estudo demonstram uma exposição elevada a diversas sorovariedades de Leptospira nos equídeos abatidos no matadourofrigorífico. Apesar da baixa frequência de animais positivos para Brucella spp., podese afirmar que a infecção ...
Keywords: Equino; Equino - Doenças; Brucelose; Leptospirose em animais; Imunoglobulinas; Matadouros; Leptospirosis in animals